ANALISIS LITERASI SAINS DAN INVENTARISASI MUATAN PENDIDIKAN KARAKTER PADA BUKU TEKS PELAJARAN IPA KELAS IX SMP - Amira Hafsari; Mariani Natalina; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aimed to describe the percentage of scientific literacy dimensions and character education content in science textbooks for junior high school grade IX. This research was carried out in Study Program Biology Education, Faculty of Teacher Training and Education, Riau University in June-November 2019. This research uses a qualitative approach with content analysis method. The research subjects is textbooks of Integrated Sciences for SMP/MTs grade IX, 2013 Curriculum revised 2018 published by Erlangga. The research instrument was the form of an assessment sheet of scientific literacy dimensions based on total of statements and the appearance of indicators along an instrument for data collection on character education content. The research was divided into 2 phases, that is the phase analysis of scientific literacy and inventory of character education content. Data analysis uses descriptive statistical methods. The results showed that highest percentage of dimensions of scientific literacy based on total of statements contained in dimensions of science as a way investigasting at 43,05%. Based on the appearance of the indicator, only the dimensions of science as the body of knowledge have good criteria with a percentage at 54%. The highest percentage of character education content is in value of hard work at 16.56%. For religious values, tolerance, love peace and social care are not found in the textbooks. The results of this research can be used in the development of science textbooks based on the content of dimensions of scientific literacy and the content of character education.Key Words: Scientific Literacy, Character Education, Textbook